Pengabdian Mahasiswa IAKN Toraja Melalui Kuliah Kerja Nyata Tematik di Lembang Salu Tapokko’, Tana Toraja - Serdianus, Serdianus; Ardano, Lucky; Biri, Agus; Bungin, Alfrida; Prinda, Almei; Bangun, Artin Sampe; Maviana, Anggryel; Asmiati, Asmiati; Tabuni, Delince; Mammai, Jandri; Bua, Janni Toding; Bumbungan, Kristin; Valengsa, Viola (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Diversity is an integral part of Indonesian society, often giving rise to conflicts that adversely affect the community. Therefore, through the implementation of the Thematic Real Work Lecture (KKN-T) in the Academic Year 2022/2023, the Research and Community Service Institute (LPPM) of IAKN Toraja focuses on the theme